2020
DOI: 10.3390/socsci9050063
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Psychosocial Therapy with SMS in Immigrant Women with Different Degrees of Depression

Abstract: Immigrant women who are forced to adapt to a new cultural context often live in low income situations, have informal jobs, and experience social inclusion difficulties; these women frequently have mental health and social relationship problems. We conducted an experimental investigation with a group of vulnerable immigrant women who were receiving support from public social services. Our goal was to analyze the effectiveness of a bio-psychosocial therapy system with text messages to personal mobile phones. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
3
11
0
1
Order By: Relevance
“…Findings of our review also indicated the benefits of using smartphone-based technology for the purposes of motivation and assistance [ 40 , 42 , 43 , 44 , 45 ]. Our findings are in accordance with other studies using phone text-message psychosocial intervention therapies, which found significant improvements in mood and depression among vulnerable groups of immigrant women, challenging previous notions that phone-based navigation for immigrants is difficult [ 62 , 63 ]. However, our findings are in contrast with another study which suggests that there may be disparities in technology-use between native older adults and immigrant older adults due to disparities in language proficiency, health literacy, socioeconomic status, education and acculturation levels [ 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…Findings of our review also indicated the benefits of using smartphone-based technology for the purposes of motivation and assistance [ 40 , 42 , 43 , 44 , 45 ]. Our findings are in accordance with other studies using phone text-message psychosocial intervention therapies, which found significant improvements in mood and depression among vulnerable groups of immigrant women, challenging previous notions that phone-based navigation for immigrants is difficult [ 62 , 63 ]. However, our findings are in contrast with another study which suggests that there may be disparities in technology-use between native older adults and immigrant older adults due to disparities in language proficiency, health literacy, socioeconomic status, education and acculturation levels [ 64 ].…”
Section: Discussionsupporting
confidence: 92%
“…It was possible to group and link recipients and messages by the degree of depression and mood of the recipient measured with the PHQ-9 to guide positive changes in behavior. Our study followed a quasi-experimental methodology and we obtained positive results comparable to those previously achieved with immigrant women [ 26 ], but the group of female victims of gender-based violence was not homogeneous in terms of age, country of origin, education, employment, or marital status.…”
Section: Discussionsupporting
confidence: 65%
“…We have no doubt that specialized software for blended therapies will have to be developed by social services professionals in an interdisciplinary collaboration with computer engineers, healthcare professionals, social workers, psychologists, and other social scientists, as stated by García, Ferrás, and Ginzo [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these included papers reporting on the same interventions or even the same study. Two studies reported a different analysis on the same data from a text- and phone-based intervention, with one comparing intervention and control groups [ 20 ] and the other analyzing data only from the intervention group [ 21 ]. There were two follow-up studies on a tablet-based intervention [ 22 ].…”
Section: Methodsmentioning
confidence: 99%